The Polish Version of the Alberta Infant Motor Scale: Cultural Adaptation and Validation - Eliks, Małgorzata; Sowińska, Anna; Gajewska, Ewa (Frontiers in Neurology, 2022)
The Alberta Infant Motor Scale (AIMS) is a diagnostic tool for the assessment of the motor performance of infants from the time of birth, to the period of independent walking (0-18 months). The aim of the study was to derive a Polish version of the Alberta Infant Motor Scale through its cultural adaptation and validation. The study included 145 infants aged 0-18 months, divided into four further age groups: 0-3 months, 4-7 months, 8-11 months, and older than 12 months. The validation was based on an analysis of intra- and interrater reliability, as well as concurrent validity, using the gross motor scale Peabody Developmental Motor Scales-2. The total Intraclass Correlation Coefficient (ICC) for intrarater reliability was 0.99 (ICC range in positions: 0.87-0.99, in subgroups: 0.91-0.99), while in particular positions, the ICC ranges were as follows: prone 0.97-0.99, supine 0.94-0.99, sitting 0.95-0.99, standing: 0.63-0.99. The total ICC for interrater reliability was 0.99 (ICC range in positions 0.98-0.99, in subgroups 0.91-0.99), while in particular positions, the ICC ranges were as follows: prone 0.95-0.99, supine 0.93-0.96, sitting 0.93-0.98, standing 0.91-0.98. Only the standing position was analyzed for the subgroup of participants over 12 months old. The Spearman correlation between the Polish version of Alberta Infant Motor Scale and gross motor scale of Peabody Developmental Motor Scales-2 was significant in total population (r= 0.97, p < 0.0001), as well as in subgroups (r=0.79-0.85, p < 0.0001). The results of our study confirm that the Polish version of the AIMS is reliable for infants aged 0-18 months and can be applied in this population for clinical and scientific purposes. Trial registry: ClinicalTrials.gov ID NCT05264064, URL https://clinicaltrials.gov/ct2/show/NCT05264064